Assessing environmental sustainability under risk and governance pressures: new insights from Canada - Ullah, Sami; Lin, Boqiang (Frontiers in Sustainable Energy Policy, 2025)
Environmental sustainability is a central concern in environmental economics, yet the effects of institutional quality and macroeconomic risks on sustainability outcomes remain underexplored, particularly in developed economies. This study examines how economic policy uncertainty (EPU), political risk (PRI), and governance quality (GOV) influence environmental sustainability in Canada, using the load capacity factor as a proxy. Utilizing quarterly data from 1990 to 2022, we apply the quantile-on-quantile regression method to capture heterogeneous and nonlinear relationships across different levels of environmental performance. Robustness is ensured through wavelet coherence analysis. The results reveal that EPU positively affects sustainability at higher quantiles, possibly due to precautionary shifts in policy or investment behavior. PRI also contributes positively in high-risk settings, reflecting the role of political institutions in environmental governance. Strong governance exhibits a consistently favorable impact across quantiles. Moreover, environmental innovation strengthens the positive effects of all three variables. These findings underscore the importance of adaptive institutions, risk-aware policymaking, and innovation-driven strategies for advancing environmental sustainability.